The Role of Freelance Live Streaming Hosts on Student Income and Trust Formation in the Perspective of Islamic Economics - Farah Urfa Majda; Fathia Salsabilla Aziza; Sarpini (Wealth: Journal of Islamic Banking and Finance, 2026)
The rapid transformation of digital technology has given birth to various innovations in the economic sector, including the emergence of new work models based on digital platforms, one of which is the profession as a freelance live streaming host which began with the Covid-19 event. This freelance live streaming host is an alternative job option for students because of its flexible work system and can be an additional source of income. This study aims to analyze the role of freelance live streaming hosts in increasing student income and the process of building trust from an Islamic economic perspective. This study uses a qualitative method with a case study approach to active students who work as live streaming hosts on digital marketplace platforms . Data were obtained through in-depth interviews, participatory observations, and documentation, then analyzed using Miles and Huberman's interactive analysis model. The results of the study show that live streaming hosting activities contribute to increasing student income through human capital development in the form of communication skills, digital literacy and marketing experience. Apart from the economic aspect, the formation of trust occurs through the application of honest, transparent, and non-exaggerated communication of product information so that it is in accordance with Islamic economic principles such as ṣidq, amanah, and justice. The trust that has been formed encourages consumers to be loyal to the company and the sustainability of business relationships. This research confirms that the success of the live streaming host profession is not only determined by the individual's technical ability, but also by the application of sharia ethical values in digital marketing activities.